2022
DOI: 10.1177/08874034221130037
|View full text |Cite
|
Sign up to set email alerts
|

Student Mentors of Incarcerated Persons: Contribution of a Mentoring Program for Incarcerated Persons

Abstract: This study evaluates the impact of a student program for mentoring incarcerated persons. Mentoring has multiple goals for both incarcerated persons and mentors; this article focuses on its contributions to incarcerated persons. The program encourages incarcerated persons to think positively and constructively, apply anger management, and learn about the normative society they will enter. Twenty-one incarcerated persons participated in semi-structured in-depth interviews in this qualitative research. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Mentorship programs connect parolees with volunteer mentors who have successfully reintegrated into society after their own involvement with the criminal justice system. Research found that mentoring has a positive effect on the rehabilitation of offenders and sustaining law-abidance among ex-offenders and parolees (Timor, Peled-Laskov & Golan, 2023). The services that volunteer mentors provide among other include guidance, support, and being role models for ex-offenders and parolees.…”
Section: Mentorship and Peer Supportmentioning
confidence: 99%
“…Mentorship programs connect parolees with volunteer mentors who have successfully reintegrated into society after their own involvement with the criminal justice system. Research found that mentoring has a positive effect on the rehabilitation of offenders and sustaining law-abidance among ex-offenders and parolees (Timor, Peled-Laskov & Golan, 2023). The services that volunteer mentors provide among other include guidance, support, and being role models for ex-offenders and parolees.…”
Section: Mentorship and Peer Supportmentioning
confidence: 99%